Epidermal Systems and Virtual Reality: Emerging Disruptive Technology for Military Applications - Marsili, M. (2nd World Conference on Advanced Materials for Defense (AuxDefense 2020 - Online Edition), 2020)
This brief study focuses on skin as sensory interface, and explores the latest discoveries in bioelectronic science. The work analyzes at what extent invisibility is possible by emulating nature, and if military applications can really benefit from technology that combines epidermal systems and virtual reality.